Pre-harvest low-dose UV-B irradiation improves the accumulation of bioactive component and post-harvest shelf-life of Mesembryanthemum crystallinum - Han Zhang; Weitang Song; Liang Zheng (Journal of Agriculture and Food Research)
At low doses, UV abiotic stressors benefit plants by stimulating the synthesis of secondary metabolites. This study initially validated the capacity of pre-harvest UV-B treatment to enhance the accumulation of bioactive compounds (mainly phenolics and flavonoids) in M. crystallinum. Subsequently, the effects of varying UV-B levels (0, 0.7, and 1.4 W/m2) on the postharvest quality were investigated by analyzing the temporal dynamics of multiple underlying factors, such as soluble protein and sugar content, weight loss, pigments (carotenoid, chlorophyll), the buildup of reactive oxygen species (ROS; H2O2, O2−), non-enzymatic antioxidants (polyphenols, ascorbic acid), and major antioxidant enzymes activity (CAT and SOD). Evaluations were carried out on excised shoots that dark-stored for 10 days (16 °C, 80 % relative air humidity). The results showed that after low-intensity UV-B treatment (0.7 W/m2), the enzymatic and non-enzymatic antioxidant machinery was more strongly stimulated to offset the accumulation of ROS. While the high-intensity UV-B (1.4 W/m2) led to a decline in soluble protein and sugar reserves over time, accompanied by an increase in ROS., Overall, the findings demonstrate a significantly intensity-dependent beneficial impact of UV-B radiation on M. crystallinum's nutritional value and shelf-life throughout growth.